Jih?d - Bonney, R. author. aut Link
XXVI, 594 p.
Keywords: Holy war ideas appear among Muslims during the earliest manifestations of the religion. This book locates the origin of Jihad and traces its evolution as an idea with the intellectual history of the concept of Jihad in Islam as well as how it has been misapplied by modern Islamic terrorists and suicide bombers.